LGBT In Criminal Code: A Dialeectics Of Morals And Human Rights From Prophetic Legal Perspective - Sophian Yahya Selajar; Enggar Wijayanto (Jurnal Hukum Samudra Keadilan, 2024)
The existence of LGBT individuals in Indonesia remains a contentious topic in society due to the perceived deviation from social norms in their orientation and behavior. Opinions on how to address LGBT individuals vary greatly, with some supporting their rights and others opposing them based on differing interpretations of human rights and moral and religious values. One prevalent discourse is to criminalize LGBT behavior as a violation of public decency in the reform of the Criminal Code. However, problems arise due to the lack of clarity in regulations and how to address the group from moral and human rights perspectives. This paper will discuss the ratio legis of LGBT regulation in national criminal law with human rights and morality variables, using the perspective of prophetic law. The data collection method is a library research model, and secondary data is used with descriptive-qualitative analysis techniques. The study found that the inclusion of LGBT elements in the national criminal law reform is a preventive measure taken by the state to curb the potential impact of LGBT on society. However, it is important to note that this reform is limited to criminal acts of decency and does not imply an implicit prohibition. It is crucial to maintain public morality without discriminating against any particular group. The principle of human rights and morals in Indonesia is based on Pancasila, which serves as the philosophical foundation and the ideals of national law. Therefore, LGBT sexual orientation and behavior are not accepted. The regulation of LGBT in the Criminal Code reaffirms the basic principles of the state built on the Almighty God and considers the legal system holistically, not limited to the principle of legal positivism, but also including morals as the substance of law.